Chasing the Shadows : How Significant is Shadow Banking in Emerging Markets? - Ghosh, Swati; Gonzalez del Mazo, Ines; Ötker-Robe, İnci (World Bank, Washington, DC, 2014)
Broadly defined as credit intermediation involving entities and activities outside the regular banking system, shadow banking raises important policy concerns. Given significant challenges with data availability, the size, nature and significance of shadow banking in emerging market and developing economies (EMDEs) are even less discussed and understood. Shadow banking in EMDEs generally does not involve long, complex, opaque chains of intermediation, as is often the case in advanced economies. Nonetheless, it can pose systemic risks, both directly, as its importance in the total financial system grows (with the concomitant credit, market, and liquidity risks that its participants undertake), and indirectly through its interconnectedness with the regulated banking system. At the same time, shadow banks also play an important role in channeling alternative funding sources to EMDEs, especially as deleveraging pressures from European banks continue. This suggests that policy makers need to manage trade-offs carefully to ensure that shadow banks provide alternative but safe sources of funding to the private sector without generating additional systemic risks. Based on a snapshot of selected EMDEs in East Asia and in Central and Eastern Europe, and subject to caveats dictated by limited data availability, the shadow banking system is relatively small in most EMDEs, but has grown markedly in recent years, reaching a not insignificant share of the financial system in some countries, while remaining largely unregulated.